2014
DOI: 10.1007/s11270-014-2181-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Plant Material as Carbon Sources on TN Removal Efficiency and N2O Flux in Vertical-Flow-Constructed Wetlands

Abstract: A nitrate-dominant synthetic wastewater simulating slightly polluted water with low C/N and poor biochemical availability was treated in lab-scale vertical-flow (VF)-constructed wetlands, which had Phragmites australis planted with different types of external carbon sources: Platanus acerifolia leaf litters, P. australis litters, glucose and a blank test with no external carbon sources. A comparison of the TN removal and N 2 O flux performances among the four wetland reactors indicated higher TN removal effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 28 publications
0
8
0
1
Order By: Relevance
“…Although the O 2 concentration and COD:N ratio influence N 2 O emissions, the high concentration of NO 2 is the most important operational parameter leading to N 2 O emissions in wastewater treatment (Kampschreur et al, 2009;Kelso et al, 1997Kelso et al, , 1999Saeed and Sun, 2012;Zhang et al, 2014). Indeed, we observed a positive correlation (r 2 = 0.870; P < 0.001) between cumulative N 2 O flux and NO 2 exposure in our CWs (Figure 3).…”
Section: Aerobic Microfloramentioning
confidence: 61%
See 2 more Smart Citations
“…Although the O 2 concentration and COD:N ratio influence N 2 O emissions, the high concentration of NO 2 is the most important operational parameter leading to N 2 O emissions in wastewater treatment (Kampschreur et al, 2009;Kelso et al, 1997Kelso et al, , 1999Saeed and Sun, 2012;Zhang et al, 2014). Indeed, we observed a positive correlation (r 2 = 0.870; P < 0.001) between cumulative N 2 O flux and NO 2 exposure in our CWs (Figure 3).…”
Section: Aerobic Microfloramentioning
confidence: 61%
“…Indeed, we observed a positive correlation (r 2 = 0.870; P < 0.001) between cumulative N 2 O flux and NO 2 exposure in our CWs (Figure 3). Similarly, a strong positive relationship between N 2 O flux and NO 2 exposure (r 2 = 0.945) was observed for VSS treating synthetic wastewater with different types of external C sources (Zhang et al, 2014). Under limited O 2 concentration, it was also reported that a NO 2 concentration higher than 50 mg N L -1 results in increased N 2 O production (Castro- Barros et al, 2016), which is in line with our FWS results where the outlet concentration of NO 2 was ~57 mg N L -1 .…”
Section: Aerobic Microfloramentioning
confidence: 68%
See 1 more Smart Citation
“…Diante dessas condições, o tempo de detenção hidráulica (TDH) é reduzido, podendo levar ao decréscimo na eficiência dos sistemas (ROUSSEAU; VANROLLEGHEM. ; DE PAUW, 2004;ZHANG et al, 2014).…”
Section: Introductionunclassified
“…The efficiency of N removal in constructed wetlands was improved via stimulated nitrification potentials by introduced earthworms 5) . Zhang et al (2014) 6) demonstrated that litter from Phragmites australis that served as an external carbon sources enhanced the total N removal efficiency, by improving the supply of organic carbon for heterotrophic denitrification. Decomposition of P. australis litter depends on faunal involvement 7) .…”
Section: Introductionmentioning
confidence: 99%